PENGARUH BUDAYA ORGANISASIONAL TERHADAP KEPUASAN KERJA MELALUI KINERJA KARYAWAN PADA KANTOR PERUM PERHUTANI UNIT II JAWA TIMUR - Reni Kusuma Wardhani (Politeknik Negeri Lhokseumawe, 2022)
Abstract: This article is to explain the relationship between organizational culture and job satisfaction through employee performance. This article explains how organizational culture is important to improve employee performance and job satisfaction. This study used 108 people as samples taken from various bureaus at Kantor Perum Perhutani Unit II, East Java. The results of this study support all hypotheses, namely organizational culture influences employee performance, organizational culture increases job satisfaction, performance affects job satisfaction, and organizational culture influences job satisfaction through employee performance. The results show that the effect is positive. The results also show that organizational culture, employee performance, and job satisfaction in this company have high values.Keywords: Organizational Culture, Job Satisfaction, Employee Performance